Outcome expectations, self-efficacy, eating environment, and eating behaviors by the stages of change in adequate sodium intake among university students: a cross-sectional study - Yeon Gyu Im; Kyung Won Kim (Korean Journal of Community Nutrition)
Objectives This study investigated whether outcome expectations, self-efficacy, eating environment, and eating behaviors differed according to the stages of change in adequate sodium intake among university students. Methods The participants were students recruited from nine universities in Seoul, Korea. An online survey was conducted, and data from 351 participants were analyzed. Participants were classified into pre-action and action stages based on adequate sodium intake. Data were analyzed using t-test, χ2-test, analysis of covariance, and correlation analysis. Results Participants in the action stage (22.8%) felt fewer disadvantages of eating sodium adequately compared to those in the pre-action stage (77.2%, P < 0.001) and perceived more self-efficacy for healthy eating behaviors (P < 0.001) and controlling sodium intake (P < 0.01). The participants in the action stage also showed more desirable eating behaviors than those in the pre-action stage, including general eating behaviors, behaviors related to sodium intake, and sodium checks (P < 0.001). The physical environment in the action stage was more supportive of adequate sodium intake (P < 0.05). Eating behaviors, self-efficacy, and outcome expectations were significantly correlated with the stages of change; however, some differences were noticed in the correlation of the subscales of variables with the stages of change when examined by sex. Conclusion We observed differences in factors according to the stages of change in adequate sodium intake. For the pre-action stage, nutrition education can be planned to modify negative expectations of eating adequate sodium, foster self-efficacy, and practice general eating behaviors and behaviors to gradually reduce sodium intake. It is also necessary to alter the physical environment to reduce sodium intake. In the action stage, support and reinforcement are needed to continually practice and maintain desirable eating behaviors. Nutrition education for women may be planned using multiple paths, whereas a simple strategy may be useful for men.